Выражение (а/a-2 - 2/a+2) (4-a^2) + a^2

755Никита7451 755Никита7451    1   03.09.2019 08:00    0

Ответы
bigofficerjor bigofficerjor  06.10.2020 14:15

1). a/a-2-2/a+2=(a^2+2a-2a+4)/a^2-4=a^2+4/a^2-4

2). -(a^2+4)/(4-a^2)*(4-a^2)=-a^2-4

3). -a^2-4+a^2=-4

ПОКАЗАТЬ ОТВЕТЫ
Щерсть Щерсть  06.10.2020 14:15
В первой скобке приведём к общему знаменателю 
((a*(a+2)-2*(a-2))/((a-2)*(a+2))*(4-a^2)+a^2=
=((a^2+2*a-2*a+4)/(a^2-4))*(4-a^2)+a^2=((a^2+4)/(a^2-4))*(-1*(a^2-4)+a^2=
=(сократим a^2-4)=-a^2-4+a^2=-4
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика